Advances in applied mathematics - Ansari, Ali R. (Springer Proceedings in Mathematics & Statistics, 2014)
This volume contains contributions from the Gulf International Conference in Applied Mathematics, held at the Gulf University for Science & Technology. The proceedings reflects the three major themes of the conference. The first of these was mathematical biology, including a keynote address by Professor Philip Maini. The second theme was computational science/numerical analysis, including a keynote address by Professor Grigorii Shishkin. The conference also addressed more general applications topics, with papers in business applications, fluid mechanics, optimization, scheduling problems, and engineering applications, as well as a keynote by Professor Ali Nayfeh.